Oxidative Status and Acute Phase Reactants in Patients with Environmental Asbestos Exposure and Mesothelioma. (23rd January 2014) - Sezgi, Cengizhan; Taylan, Mahsuk; Selimoglu Sen, Hadice; Evliyaoğlu, Osman; Kaya, Halide; Abakay, Ozlem; Abakay, Abdurrahman; Tanrıkulu, Abdullah Cetin; Senyiğit, Abdurrahman
Abstract : Background and Objectives . The aim of this study was to investigate inflammatory indicators and oxidative status in patients with asbestos exposure with and without mesothelioma and to compare results with data from healthy subjects. Methods . Eighty people with exposure to environmental asbestos and without any disease, 46 mesothelioma patients, and a control group of 50 people without exposure to environmental asbestos were enrolled in this prospective study. Serum total oxidant level (TOL), total antioxidant capacity (TAC), and oxidative stress index (OSI), CRP, transferrin, ceruloplasmin, α -1 antitrypsin, ferritin, and copper levels were measured. Results . Mesothelioma group exhibited higher TOL, OSI, α 1-antitrypsin, ferritin and copper levels as compared to the other groups (P < 0.001, P = 0.007, P < 0.0001, P < 0.001, and P < 0.001, resp.). Transferrin was lower in the mesothelioma group than in the other two groups (P < 0.001 ). The asbestos group had higher TOL, TAC, α 1-antitrypsin, and transferrin levels (P < 0.001, P < 0.001, P < 0.001, and P < 0.001, resp.), as well as lower OSI and ferritin levels as compared to the control group (P < 0.001 and P < 0.001 ). Conclusions . We believe that elevated acute phase reactants and oxidative stress markers (TOL and OSI) in the mesothelioma group can be used as predictive markers for the development of asbestos-related malignancy.